Verbal and Non-Verbal Sign on Inflight E-Magazine Garuda Indonesia “Colours” - Ni Putu Chika Maho Dewi; Ida Bagus Gde Nova Winarta (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study focuses on semiotic analysis and explains the meanings expressed by both verbal and non-verbal sign in Garuda Indonesia's in-flight e-magazine